Labour intermediation services : lessons for Latin America and the Caribbean - Mazza, Jacqueline (2003)
Reviews the modern concept of labour intermediation, outlining its various services. Analyzes OECD and Latin American experience with reform and modernization of intermediation systems with an eye to recommendations and adaptations particularly relevant to economies in the region.